An adaptive velocity planning method for multi-DOF robot manipulators. (18th May 2017) - Gao, Mingyu; Li, Zhong; He, Zhiwei; Li, Xiao
Multi-degrees of freedom robot manipulators are widely used in the manufacturing areas. Trajectory planning of the end effector is the most important while the hardest task for the use of the manipulators. An adaptive velocity planning method for multi-degrees of freedom robots with a predefined path is proposed in this article, which is based on interpolation technology. A resolved motion acceleration control strategy based on a fixed-distance movement is proposed, along with an adaptive time interpolation correction algorithm to achieve the speed planning for multi-degrees of freedom manipulators. Besides the accuracy and efficiency, more attentions were paid on the velocity control at turning points along the path, so that a transient vibration and a transient overshoot can be avoided, leading to a stable movement of the robot. A fold line trajectory and a circular-line connected trajectory were implemented on a 6-degrees of freedom robot manipulator. Simulations and experimental results show that the proposed method is efficient and effective.